Clinical implications of the Royal College of Physicians three questions in routine asthma care: a real-life validation study - Pinnock, Hilary (Prim Care Respir J, 2012)
BACKGROUND: Annual recording of the Royal College of Physicians three questions (RCP3Q) morbidity score is rewarded within the UK ‘pay-for-performance’ Quality and Outcomes Framework. AIMS: To investigate the performance of the RCP3Q for assessing control in real-life practice compared with the validated Asthma Control Questionnaire (ACQ) administered by self-completed questionnaire. METHODS: We compared the RCP3Q score extracted from a patient's computerised medical record with the ACQ self-completed after the consultation. The anonymous data were paired by practice, age, sex, and dates of completion. We calculated the sensitivity and specificity of the RCP3Q scale compared with the threshold for good/poor asthma control (ACQ ≥1). RESULTS: Of 291 ACQ questionnaires returned from 12 participating practices, 129 could be paired with complete RCP3Q data. Twenty-five of 27 patients who scored zero on the RCP3Q were well controlled (ACQ <1). An RCP3Q score ≥1 predicted inadequate control (ACQ ≥1) with a sensitivity of 0.96 and specificity of 0.34. Comparable values for RCP3Q≥2 were sensitivity 0.50 and specificity 0.94. The intraclass correlation coefficient of 0.13 indicated substantial variability between practices. Exacerbations and use of reliever inhalers were moderately correlated with ACQ (Spearman's rho 0.3 and 0.35) and may reflect different aspects of control. CONCLUSIONS: In routine practice, an RCP3Q score of zero indicates good asthma control and a score of 2 or 3 indicates poor control. An RCP3Q score of 1 has good sensitivity but poor specificity for suboptimal control and should provoke further enquiry and consideration of other aspects of control such as exacerbations and use of reliever inhalers.